Csseverin inhibits apoptosis through mitochondria-mediated pathways triggered by Ca(2 +) dyshomeostasis in hepatocarcinoma PLC cells - Shi, Mengchen (PLoS Negl Trop Dis, 2017)
BACKGROUND: Numerous experimental and epidemiological studies have demonstrated a link between Clonorchis sinensis (C. sinensis) infestation and cholangiocarcinoma (CCA) as well as hepatocellular carcinoma (HCC). The underlying molecular mechanism involved in the malignancy of CCA and HCC has not yet been addressed. Csseverin, a component of the excretory/secretory products of C. sinensis (CsESPs), was confirmed to cause obvious apoptotic inhibition in the human HCC cell line PLC. However, the antiapoptotic mechanism is unclear. In the present study, we investigated the cellular features of the antiapoptotic mechanism upon transfection of the Csseverin gene. METHODS: In the present study, we evaluated the effects of Csseverin gene overexpression on the apoptosis of PLC cells using an Annexin PE/7-AAD assay. Western blotting was applied to quantify the activation of caspase-3 and caspase-9, the mitochondrial translocation of Bax and the release of Cyt c upon Csseverin overexpression in PLC cells. Laser scanning confocal microscopy was used to analyze the changes of intracellular calcium. Fluorescence assay and immunofluorescence assays were performed to observe the changes of the mitochondrial permeability transition pore (MPTP). RESULTS: The overexpression of Csseverin in PLC cells showed apoptosis resistance after the induction of apoptosis. Additionally, the activation of caspase-3 and caspase-9 was specifically weakened in Csseverin overexpression PLC cells. The overexpression of Csseverin reduced the increase in intracellular free Ca2+, thereby inhibiting MPTP opening in PLC cells. Moreover, Bax mitochondrial translocation and the subsequent release of Cyt c were downregulated in apoptotic Csseverin overexpression PLC cells. CONCLUSIONS: The present findings suggest that Csseverin, a component of CsESPs, confers protection from human HCC cell apoptosis via the inactivation of membranous Ca(2+) channels. Csseverin might be involved in the process of HCC through C. sinensis infestation in affected patients.